Immunomodulatory action of Copaifera spp oleoresins on cytokine production by human monocytes - Santiago, Karina Basso [UNESP]; Conti, Bruno José [UNESP]; Andrade, Bruna Fernanda Murbach Teles [UNESP]; Silva, Jonas Joaquim Mangabeira da; Rogez, Herve Louis Ghislain; Crevelin, Eduardo José; Moraes, Luiz Alberto Beraldo de; Veneziani, Rodrigo; Ambrósio, Sérgio Ricardo; Bastos, Jairo Kenupp; Sforcin, José Maurício [UNESP] (Elsevier B.V., 2015)
Copaifera spp oleoresins have been used in folk medicine for centuries; nevertheless, its immunomodulatory action has not been investigated. Thus, the goal of this study was to characterize different oleoresins and to verify their action on human monocytes regarding pro-and anti-inflammatory cytokine production (TNF-alpha and IL-10, respectively). The chemical composition of Brazilian Copaifera reticulata, Copaifera duckey and Copaifera multijuga oleoresins was analyzed by HPLC-MS. Cell viability was assessed by MTT method after incubation of cells with Copaifera spp. Noncytotoxic concentrations of oleoresins were incubated with human monocytes from healthy donors, and cytokine production was determined by ELISA. HPLC-MS analysis for terpenes allowed the identification of six diterpene acids and one sesquiterpene acid. Oleoresins exerted no cytotoxic effects on human monocytes. All oleoresins had a similar profile: LPS-induced TNF-alpha production was maintained by oleoresins, while a significant inhibitory action on IL-10 production was seen. Copaifera oleoresins seemed to exert an activator profile on human monocytes without affecting cell viability. Such effect may be due to the presence of either diterpene or sesquiterpene acids; however, further studies are necessary to determine the involvement of such compounds in Copaifera immunomodulatory effects.
Keywords: Copaifera oleoresins; Cytokines; Monocytes